Low-molecular weight heparin protamine complex augmented the potential of adipose-derived stromal cells to ameliorate limb ischemia. (June 2016) - Kishimoto, Satoko; Inoue, Ken-ichi; Nakamura, Shingo; Hattori, Hidemi; Ishihara, Masayuki; Sakuma, Masashi; Toyoda, Shigeru; Iwaguro, Hideki; Taguchi, Isao; Inoue, Teruo; Yoshida, Ken-ichiro
Abstract: Background and aims: Heparin/protamine micro/nanoparticles (LH/P-MPs) were recently developed as low-molecular weight, biodegradable carriers for adipose-derived stromal cells (ADSCs). These particles can be used for a locally delivered stem cell therapy that promotes angiogenesis. LH/P-MPs bind to the cell surface of ADSCs and promote cell-to-cell interaction and aggregation of ADSCs. Cultured ADSC/LH/P-MP aggregates remain viable. Here, we examined the ability of these aggregates to rescue limb loss in a mouse model of hindlimb ischemia. Methods: Unilateral hindlimb ischemia was induced in adult male BALB/c mice by ligation of the iliac artery and hindlimb vein. For allotransplantation of ADSCs from the same inbred strain, we injected ADSC alone or ADSC/LH/P-MP aggregates or control medium (sham-treated) directly into the ischemic muscles. Ischemic limb blood perfusion, vessel density, and vessel area were recorded. The extent of ischemic limb necrosis or limb loss was assessed on postoperative days 2, 7, and 14. Results: Compared with the sham-treatment control, treatment with ADSCs alone showed modest effects on blood perfusion recovery and increased the number of α-SMA-positive vessels. Response to ADSC/LH/P-MP aggregates was significantly greater than ADSCs alone for every endpoint. ADSC/LH/P-MP aggregates more effectively prevented the loss of ischemic hindlimbs than ADSCs alone or the sham-treatment. Conclusion: The LH/P-MPs augmented the effects of ADSCs on angiogenesis and reversal of limb ischemia. Use of ADSC/LH/P-MP aggregates offers a novel and convenient treatment method and potentially represents a promising new therapeutic approach to inducing angiogenesis in ischemic diseases. Highlights: LH/P-MPs promote cell-to-cell interaction and the aggregation of mouse ADSCs. When ADSC/LH/P-MP aggregates are cultured, LH/P-MPs maintain their viability. ADSCs/LH/P-MPs promote neovascularization and prevent ischemic limb loss in mice. Use of ADSC/LH/P-MPs offers a convenient treatment method in ischemic diseases.